Existential boredom as a phenomenon of human social existence - Svetlana M. Maltseva; Polina O. Ivanova; Olga P. Kashina (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. Until now, science lacks a holistic philosophical understanding of the phenomenon of existential boredom and has not developed an attitude towards it, although it is recognized in the scientific community. The problem is that in today's rapidly changing and constantly evolving world, people are losing their spiritual and moral bearings, suffering from boredom. This article allows us to consider existential boredom as its variety from various points of view.